An exploration and description of experiences of at-risk youth in a correctional center in Eswatini regarding a resilience intervention program - Shabangu, Sifiso B.; Koen, Vicki (Frontiers in Psychology, 2022)
Resilience-focused programs advocate nurturing positive adoptive traits to inform prevention and intervention efforts. Considering that no resilience intervention programs have been developed specifically for at-risk youth in correctional centers in Eswatini, the authors developed a program with this focus through a combination of literature review and earlier empirical research with correctional officers and youth in a correctional center in Eswatini. This study aimed to evaluate the program through exploration and description of experiences of at-risk youth in a correctional center in Eswatini regarding the program. A purposive sample of 16 youths in a correctional center in Eswatini participated in a World Café, and data were analyzed thematically. Three themes were identified: Positive outcomes of participation, challenges encountered in the program, and recommendations for the program.